1986
DOI: 10.1002/(sici)1097-4571(198607)37:4<197::aid-asi4>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Views on end-user searching

Abstract: Online searching is a changing, evolving portion of the information industry. During the past 10 years, it has moved from libraries into homes and offices creating a group of people called end-user searchers. The definition of end-user searchers distinguishes them from intermediary searchers, but a demographic profile is unavailable. End-user searchers perform online searches for a variety of reasons; past trends indicate that enduser searching will increase. This probable increase has significant implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Ojala (1986, p. 197) points out that the first definition of end-user appeared during this time in a technical glossary of the International Business Machines Corporation (IBM). Ojala (1986) defines end-user as "a person accessing online databases and performing search operations for the purpose of finding information to be used by that same person rather than another." Arnold (1984, p. 71) defines end-users as those who use an IS, internet-based or not, to seek specific information.…”
Section: Users and End-usersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ojala (1986, p. 197) points out that the first definition of end-user appeared during this time in a technical glossary of the International Business Machines Corporation (IBM). Ojala (1986) defines end-user as "a person accessing online databases and performing search operations for the purpose of finding information to be used by that same person rather than another." Arnold (1984, p. 71) defines end-users as those who use an IS, internet-based or not, to seek specific information.…”
Section: Users and End-usersmentioning
confidence: 99%
“…During this stage, this concept of end-user narrows further, so that it is limited to researchspecialized generalists. This narrow definition is strongly influenced by academic organizations, which developed databases of books and periodicals during the 1980s (Ojala, 1986;Bourne & Robinson, 1980).…”
Section: Users and End-usersmentioning
confidence: 99%
“…Numerous studies have demonstrated that the importance of library service is users-oriented and the needs of meeting their demand and expectation [1][2][3][4][5][6][7][8]. The proliferation of information technology (IT) brings users" needs for timelier, convenient, speedy information delivery in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Here, it is clear, the first incongruity arises: is the end-user the one who uses the system and the product ± the end-user searcher ± or, for our purposes, is the end-user anybody who uses the product ± namely, the information? In her article``Views on end-user searching'' in JASIS, Ojala (1986) considers IBM's and the SNA network's definitions of an end-user. Both relate to use of the system, which in their case is also the product.…”
Section: Introductionmentioning
confidence: 99%